Species-specific predation determines the feeding impacts of six soil protist species on bacterial and eukaryotic prey - Berlinches de Gea, Alejandro; Geisen, Stefan; Grootjans, Franka; Wilschut, Rutger A.; Schwelm, Arne (European journal of protistology, 2024)
Predatory protists play a central role in nutrient cycling and are involved in other ecosystem functions by predating the microbiome. While most soil predatory protist species arguably are bacterivorous, some protist species can prey on eukaryotes. However, studies about soil protist feeding mainly focused on bacteria as prey and rarely tested both bacteria and eukaryotes as potential prey. In this study, we aimed to decipher soil predator–prey interactions of three amoebozoan and three heterolobosean soil protists and potential bacterial (Escherichia coli; 0.5–1.5 µm), fungal (Saccharomyces cerevisiae; 5–7 µm) and protist (Plasmodiophora brassicae; 3–5 µm) prey, either as individual prey or in all their combinations. We related protist performance (relative abundance) and prey consumption (qPCR) to the protist phylogenetic group and volume. We showed that for the six soil protist predators, the most suitable prey was E. coli, but some species also grew on P. brassicae or S. cerevisiae. While protist relative abundances and growth rates depended on prey type in a protist species-specific manner, phylogenetic groups and volume affected prey consumption. Yet we conclude that protist feeding patterns are mainly species-specific and that some known bacterivores might be more generalist than expected, even preying on eukaryotic plant pathogens such as P. brassicae.